Two new species in the genus Destinoides (Hemiptera: Cicadellidae, Ledrinae) from China, with DNA barcoding data - Huang, Weijian; Zhang, Yalin (Zootaxa, 2019)
Two new species in the genus Destinoides Cai & He, D. hainanensis and D. rubeus spp. nov. from China are described and illustrated. A checklist and key to the known species of Destinoides are provided.